2011
DOI: 10.1002/adfm.201100265
|View full text |Cite
|
Sign up to set email alerts
|

Array of Single‐Walled Carbon Nanotube Intrajunction Devices Fabricated via Type Conversion by Partial Coating with β‐Nicotinamide Adenine Dinucleotide

Abstract: The fabrication of aligned single-walled, carbon nanotube (SWCNT) intratube junction devices by partially coating pristine SWCNTs with a β -nicotinamide adenine dinucleotide (NADH) solution and subsequent annealing at 150 ° C is reported. Gate-bias-dependent rectifi cation behavior is observed with a rectifi cation ratio of > 10 3 at ± 1 V. A comparative study with p-n-junction devices of randomly networked SWCNTs confi rms the advantage of using aligned SWCNTs with substantially better rectifying characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…This demonstrates that the thermal annealing of NADH induces the donation of electrons via detachment of a hydrogen atom from NADH, resulting in n‐doping of SWCNTs. In our previous work, it was reported that the device performance of SWCNT homo‐junction diode fabricated via n‐doping by NADH was deteriorated in air ambient, but its instantaneous recovery was achieved by simple annealing at 150 °C for 5 min. Since water molecules adsorbed on NADH take electrons from SWCNTs, annealing can induce the desorption of water to keep the n‐type property of NADH‐coated SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates that the thermal annealing of NADH induces the donation of electrons via detachment of a hydrogen atom from NADH, resulting in n‐doping of SWCNTs. In our previous work, it was reported that the device performance of SWCNT homo‐junction diode fabricated via n‐doping by NADH was deteriorated in air ambient, but its instantaneous recovery was achieved by simple annealing at 150 °C for 5 min. Since water molecules adsorbed on NADH take electrons from SWCNTs, annealing can induce the desorption of water to keep the n‐type property of NADH‐coated SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Coating of electron‐donating poly(ethylenimine) onto the pristine SWCNTs was observed to induce n‐type properties, but it was not stable under humid ambient so that it recovered the intrinsic p‐type properties within a few days . In our previous work, we could successfully fabricate the stable intra‐tube junction diode via type‐conversion of pristine SWCNTs by partial coating with β‐nicotinamide adenine dinucleotide, reduced dipotassium salt (NADH), and subsequent annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Using Joule heating to achieve the selective removal of metallic SWNTs has many advantages, including high selectivity for metallic CNTs, a lack of specificity for nanotube diameter, and removal of the entire length of unwanted CNTs. [6a,19] We combined our fabrication technique with the Joule heating method to fabricate the suspended SWNT array field effect transistors. Figure a shows the etching of metallic SWNTs by electrical breakdown at room temperature in air.…”
Section: Resultsmentioning
confidence: 99%
“…[3a,5] Although this method avoids the resist contaminate, the nanotubes are slack and attached to a surface, rather than being clamped between pairs of contacts. In a technological application of transistors, each transistor will require several parallel CNT channels to drive the required current . Worldwide efforts are in progress to produce large‐scale nanotube arrays with a small distance between SWNTs.…”
Section: Introductionmentioning
confidence: 99%
“…The significantly enhanced unbalanced conductive behavior of the DPP4T/ SBFdiyne-COF heterojunction is ascribed to the formation of a p-n junction, which shows vastly different energy band structures under different bias voltages. [48][49][50][51] In this p-n junction, DPP4T and the SBFdiyne-COF act as p and n type semiconductors, respectively (Figure S12A). The conductive and valence bands of the SBFdiyne-COF were determined by measuring its optical band gap (Figure S13) and UPS width (Figure S14), respectively, whereas these parameters were already known for DPP4T.…”
Section: Cof/semiconductor Heterojunctionmentioning
confidence: 99%